2016
DOI: 10.1021/acs.jpclett.6b00517
|View full text |Cite
|
Sign up to set email alerts
|

All-Atom Molecular Dynamics of Virus Capsids as Drug Targets

Abstract: Virus capsids are protein shells that package the viral genome. Although their morphology and biological functions can vary markedly, capsids often play critical roles in regulating viral infection pathways. A detailed knowledge of virus capsids, including their dynamic structure, interactions with cellular factors, and the specific roles that they play in the replication cycle, is imperative for the development of antiviral therapeutics. The following Perspective introduces an emerging area of computational b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 82 publications
(158 reference statements)
2
70
0
Order By: Relevance
“…In addition, experiments do not resolve some parts of the viral particles (typically flexible or disordered) that can be important for the structure and the dynamics of the virus. 1,2 …”
mentioning
confidence: 99%
“…In addition, experiments do not resolve some parts of the viral particles (typically flexible or disordered) that can be important for the structure and the dynamics of the virus. 1,2 …”
mentioning
confidence: 99%
“…A comparison between the size of the system of interest and the timescales achievable by different molecular computational modeling techniques including molecular dynamics (MD), coarse‐grained MD, Brownian dynamics, agent‐based modeling . Examples of studies employing these approaches are provided as references.…”
Section: Agent‐based Modeling (Abm): Bridging the Gap Between High Rementioning
confidence: 99%
“…Capsids generally represent the largest protein components of virus structures, and simulations of intact capsids have accounted for the most substantial all-atom virus simulations yet published [106, 2]. Work by Perilla et al has clearly demonstrated the need for chemical detail to facilitate accurate simulation studies of virus capsids as drug targets [107]. …”
Section: Capsidsmentioning
confidence: 99%
“…The results of the work implicate the triangular pores as the extrusion site of the capsid’s carboxy-terminal domain tails, which contain cellular signals, and suggest a mechanism by which the capsid could modulate signal exposure based on tail phosphorylation. Simulations have also been used to investigate the effects of small-molecule drugs on HBV capsid morphology [107] and to determine the structural basis for enhanced assembly and drug resistance in HBV capsid mutants [117]. …”
Section: Capsidsmentioning
confidence: 99%